Gastroduodenal gastrointestinal stromal tumour: a case series and review of literature - Abuji, Kishore; Dahiya, Divya; Banda, Ashwin; Rana, Surinder S.; Behera, Arunanshu (International Surgery Journal, 2023)
Gastrointestinal stromal tumour (GIST) is the most common non-epithelial mesenchymal tumour and comprises 0.1-3% of all gastrointestinal (GI) tract tumours. They express tyrosine kinase and are potentially malignant. Therefore, early diagnosis and surgical resection is the key for good outcome. This is a retrospective analysis of medical records of five patients of gastroduodenal GIST who were managed in the department of surgery between 2014 and 2015. Demographic profile, clinical presentation, laboratory parameters, diagnostic imaging, treatment details, histopathology and long-term outcome was analysed. Patients were followed up regularly in surgery outpatient clinic. Last follow up was in December 2022. All were female; three of them presented with melena and two with lump abdomen. Patients with gastric GIST underwent sleeve resection in two and antrectomy in one patient. Patient with duodenal GIST underwent excision of tumour with primary repair of duodenum. Fifth patient had metastatic duodenal GIST; Imatinib was started in view of irresectable disease at presentation. However, there was tumour progression and she succumbed to illness seven months after treatment initiation with Imatinib. Histopathology revealed low grade GIST in two, intermediate grade in one and malignant in one. Patient with malignant GIST received Imatinib for 2 years. All four patients are well on follow up with no sign of local and distant recurrence.